2015
DOI: 10.1051/0004-6361/201425449
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of the HAT-P-23 and WASP-48 planetary systems from multi-colour photometry

Abstract: Context. Accurate and repeated photometric follow-up observations of planetary transit events are important to precisely characterize the physical properties of exoplanets. A good knowledge of the main characteristics of the exoplanets is fundamental in order to trace their origin and evolution. Multi-band photometric observations play an important role in this process. Aims. By using new photometric data, we computed precise estimates of the physical properties of two transiting planetary systems at equilibri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
4
27
2
Order By: Relevance
“…Maciejewski et al (2018) presented several new transit times and renanalyzed some light curves drawn from the literature. Their revised transit times differ from those reported by Ciceri et al (2015) by several minutes, for unknown reasons. We have adopted their rean- alyzed transit times, figuring that the more homogeneous analysis was preferable.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Maciejewski et al (2018) presented several new transit times and renanalyzed some light curves drawn from the literature. Their revised transit times differ from those reported by Ciceri et al (2015) by several minutes, for unknown reasons. We have adopted their rean- alyzed transit times, figuring that the more homogeneous analysis was preferable.…”
Section: Introductionmentioning
confidence: 56%
“…Timing residuals for HAT-P-23 b. White points are data obtained and reanalyzed byMaciejewski et al (2018) and originally reported byBakos et al (2011);Ramón-Fox & Sada (2013);Ciceri et al (2015) andSada & Ramón-Fox (2016). Black points represent new data.…”
mentioning
confidence: 90%
“…For the dayside emission spectra they fitted a blackbody model with an effective temperature of T eff = 2158 ± 100 K. Using the models of Fortney et al (2008) and Burrows et al (2008) to fit their data, they deduced that WASP48b has a weak or absent temperature inversion. Ciceri et al (2015) presents a follow up of this system using multicolor broadband photometry; this work updated the stellar parameters of WASP-48 (M = 1.062 ± 0.074 M , R = 1.519 ± 0.007 R ), measured a smaller planetary radius (R = 1.396 ± 0.051 R Jup ), and found a flat transmission spectrum using broadband filters. Turner et al (2016) presents ground-based near-UV data of several transiting systems including WASP-48b, and found a R p /R s for the U band of 0.0916 ± 0.0017, a shallower transit depth than the one found by Enoch et al (2011).…”
Section: Introductionmentioning
confidence: 93%
“…The orbital eccentricity and period were fixed to 0 and 2.14363544 days (Ciceri et al 2015), respectively. In addition to the free transit parameters, we also set as free the coefficients used to model the systematic trends present in the light curves.…”
Section: Fitting Proceduresmentioning
confidence: 99%
See 1 more Smart Citation